2023
DOI: 10.1071/mf22173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal accumulation on oxidative metabolism of

Abstract: Context Bivalve fishery represents an important socio-economic resource in Río Negro province, and Mytilus platensis is the main exploited species. Thus, biomonitoring trace metals in this mussel is particularly relevant for both environmental protection and human consumption. Aim Anthropogenic pollution and its environmental impact on mussels were experimentally evaluated in situ in two coastline sites of northern Patagonia. Methods Trace metal concentrations were quantified in the water of a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
1
0
0
Order By: Relevance
“…These results could indicate higher cellular activity due to stress factors and/or pollutants found in this study region, corroborating that human activity is more intense in AP. Morphological alterations in the digestive glands similar to those observed in this study were also found in eld oysters such as M. gigas, Magallana angulate ( Sabatini et al 2023). The change of the cell-type, also called cell-type replacement and the integrity of the digestive gland tissue, possibly occur through a loss of digestive cells and hypertrophy of basophilic cells (Marigómez et al 2006;Zaldibar et al 2007) and the extent of the interstitial connective tissue, can provoke disturbance in the metabolisms, accumulation of xenobiotics and in the food digestion (Marigómez et al 1998).…”
Section: Discussionsupporting
confidence: 87%
“…These results could indicate higher cellular activity due to stress factors and/or pollutants found in this study region, corroborating that human activity is more intense in AP. Morphological alterations in the digestive glands similar to those observed in this study were also found in eld oysters such as M. gigas, Magallana angulate ( Sabatini et al 2023). The change of the cell-type, also called cell-type replacement and the integrity of the digestive gland tissue, possibly occur through a loss of digestive cells and hypertrophy of basophilic cells (Marigómez et al 2006;Zaldibar et al 2007) and the extent of the interstitial connective tissue, can provoke disturbance in the metabolisms, accumulation of xenobiotics and in the food digestion (Marigómez et al 1998).…”
Section: Discussionsupporting
confidence: 87%